Brown Tumor of Lower Right Limb in Patients With Primary Hyperparathyroidism: A Case Report - Iqbal, Muhammad; Syafril, Santi (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2021)
Background.Brown tumor of Hyperparathyroidism is a metabolic disorder that can affect the entire skeleton and reactive process due to bone resorption caused by primary or secondary hyperparathyroidism (HPT). Brown tumors can occur as solitary or multiple lesions in any bone, most often in the pelvis, ribs, clavicle, mandibula, and extremities. Here, we report the Brown tumor in the lower right limb in patients with primary HPT, and the literature is reviewed. Case presentation. Patients was women 30 years old had married and come with main complains of difficulty walking. This condition has been experienced by patients since diagnosis with lunb of tibia last 8 months and caused pain from hip to lower leg.Â  On laboratory results, it showed elevated PTH 1.249 (normal 15-65) pg/dL, elevated phosphatase alkali 1156 (normal 40-150) u/dL, elevated Ca 10,8 (n:8,6 -10,3) mg/dL, phosphor 2,1 (3â€“4,5) mg/dL. Histology examination of tibia lump was a benign lesion of bone (Brown Tumor). Ultrasonography transabdominal result revealed kidney stones with bilateral renal pelvis dilation, nephrolithiasis non-obstructive was found with size 1 cm & left kidney cyst with size 0.6 cm. On Neck USG showed giant cyst lesion on parathyroid glands. Radiologist pelvic examination results showed bone metastasis disease. Head CT Scan examination concluded as suspect metastatic bone. Body bone scans examination showed pathological bone metastatic process. Conclusion. Brown tumor in right lower limb caused by primary HPT